Salaam (islamiat ki chatti kitab ) - Farhat Jahan (Oxford University Press Pakistan, 2014)
"Salaam (Islamiyat ki chatti Kitab)" is an Islamic studies textbook that explores foundational Islamic concepts, practices, and values for young learners.